2011
DOI: 10.1186/1472-6947-11-15
|View full text |Cite
|
Sign up to set email alerts
|

The role of the user within the medical device design and development process: medical device manufacturers' perspectives

Abstract: BackgroundAcademic literature and international standards bodies suggest that user involvement, via the incorporation of human factors engineering methods within the medical device design and development (MDDD) process, offer many benefits that enable the development of safer and more usable medical devices that are better suited to users' needs. However, little research has been carried out to explore medical device manufacturers' beliefs and attitudes towards user involvement within this process, or indeed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
166
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(178 citation statements)
references
References 27 publications
1
166
0
11
Order By: Relevance
“…Thematic analysis has been successfully used to account for phenomena underpinning medical device design, development, purchasing and use (e.g. (Cafazzo et al, 2012;Money et al, 2011;Vincent et al, 2014)); we were expecting the analysis to provide a similar degree of insight in this case.…”
Section: Coding Processmentioning
confidence: 99%
“…Thematic analysis has been successfully used to account for phenomena underpinning medical device design, development, purchasing and use (e.g. (Cafazzo et al, 2012;Money et al, 2011;Vincent et al, 2014)); we were expecting the analysis to provide a similar degree of insight in this case.…”
Section: Coding Processmentioning
confidence: 99%
“…However, based on previous research, it is not expected that this significantly influenced the results. 35,36 In addition, by giving the participants the choice to fill out the questionnaire on paper or via the Internet, a broader study sample was covered.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Despite its potential, eHealth is not being adopted and implemented successfully in daily care routines. 36,37 The Dutch Ministry of Health, Welfare and Sport acknowledges the potential benefits of eHealth and the lack of implementation and actual use. In 2014, the Minister of Health, Welfare and Sport, Edith Schippers, formulated three ambitions concerning eHealth which should be realized within five years.…”
mentioning
confidence: 99%
“…for smaller companies and those that are new to healthcare [9]. The design decisions that result from such testing require interpretation of the data, and so a lack of expertise or knowledge may prevent manufacturers from getting the most out of their usability studies [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown a similar link for medical devices [6] and so healthcare regulators are increasingly turning to usability testing [7][8][9][10]. Regulators in Europe and the USA now stipulate a formal approach to development known as human factors engineering (also known as usability engineering or user-centred design) [11], where usability is integrated into the entire development cycle rather than being assessed just prior to the release of the product.…”
Section: Introductionmentioning
confidence: 99%